Angular alignment, rotational profile, and joint range of motion in the lower limb of typically developing children from 7–16 years of age: a cross-sectional study - Christian Wong; Michael Mørk Petersen; Trine Henriksen; Ales Jurca; Soeren Boedtker; Andreas Balslev-Clausen; Steen Harsted (Acta Orthopaedica)
Background and purpose: We aimed to update reference intervals for anthropometric parameters for the passive joint range of motion (ROM), rotational profile, and angular alignment of the lower limb in typically developing children (TDC), to compare the association of the variables age, left–right sidedness, body mass index (BMI), and sex. Methods: We conducted a cross-sectional study in a convenience sample of TDC from the 1st, 5th, and 9th grades (6–17 years) in a randomized selection of Danish primary schools. We examined the anthropometric parameters in a non-clinical setting. Descriptive statistics were used to characterize the data. To explore potential differences across the variables, we utilized Bonferroni-corrected Welch’s 2-sample t-tests, one-way analysis of means, and univariable linear regression. Results: We analyzed the associations between the variables and the anthropometric parameters in 501 TDC, aged 6 to 17 years. We found a statistically significant, but not clinically meaningful decrease in ROM for the hip, knee, and ankle as well as decreased femoral anteversion and increased tibial torsion with increasing age, but no association with sex or sidedness. However, several associations between BMI and ROM measurements were statistically significant and potentially clinically meaningful, with ROM decreasing by approximately 0.4° to 1.2° per unit increase in BMI, particularly for hip, knee, and ankle flexion movements. Conclusion: Anthropometric parameters remain clinically stable after 7 years of age and are affected only by the BMI but not sex or age. We found a statistically significant but not clinically relevant decrease in torsion and joint ROM with increasing age.